Properties of pervious concrete – A state of the art review. (2021) - Elango, K.S.; Gopi, R.; Saravanakumar, R.; Rajeshkumar, V.; Vivek, D.; Raman, S. Venkat
Abstract: In recent scenario, ground water retention plays major key role in gaining environmental sustainability. This can be achieved by using pervious concrete as a pavement material in pathways, parking lots, garden areas and low traffic road applications. Many researches have been carried out by using alternate materials as a partial replacement for cement and aggregates. This paper reviews the developments in the field of pervious concrete using alternate construction materials. The research findings on mechanical, physical and durability studies have been reviewed. Clogging effects on pervious concrete also has been reviewed. This review paper mainly focussed on the various properties of pervious concrete based on the types of binders, admixtures and size of coarse aggregates. The laboratory investigations made on pervious concrete in terms of strength, permeability, porosity, density and durability were reviewed and briefly discussed. Due to expanding applications in pervious concrete because of its environmental benefits, this review paper helps the researchers to undergo future research and to understand the behaviour of pervious concrete using different types of binder and different sizes of coarse aggregates.